Percutaneous Cholecystostomy: Procedural Guidance and Future Directions for Clinical Management - Koushesh, Pouria; Ayaz, Talha; Tullius, Thomas (Seminars in Interventional Radiology, 2024)
Percutaneous cholecystostomy (PC) is a recognized treatment option for the management of acute cholecystitis and is an integral component of the treatment algorithm in the 2018 Tokyo Guidelines. The utilization of PC has significantly increased over the past 30 years, particularly in the setting of critically ill patients and those with extensive comorbidities who are poor surgical candidates. The indications, complications, patient selection considerations, and technical complexities of the procedure will be discussed. Postprocedural drain management and the potential for shortened indwelling time are reviewed.
Keywords: percutaneous cholecystostomy; acute cholecystitis; gallstones; interventional radiology